The dynamic connectedness between collateralized loan obligations and major asset classes: A TVP-VAR approach and portfolio hedging strategies for investors - Spyros Papathanasiou; Drosos Koutsokostas; Georgios Pergeris; Dimitris Kenourgios (Empirical Economics, 2024)
Motivated by the increasing demand for alternative assets that can contribute to reducing portfolio risk under inflationary environments, this paper examines the volatility spillovers between collateralized loan obligations (CLOs) and various assets used for protection against inflation, including equities, bonds, crude oil, commodities, gold, bitcoin, shipping and real estate. The applied methodology comprehends the time-varying parameter vector autoregressive (TVP-VAR) model of Antonakakis et al (2020), which relies on the classical Diebold and Yilmaz (2012) approach, for the period from January 1, 2012 to December 31, 2021. The empirical findings show moderate levels of dynamic connectedness; albeit several external shocks, such as the oil price plummet, the US-China trade war and COVID-19, strengthened the interconnection among the assets. Equities, commodities, bitcoin, real estate and gold form the net senders of spillovers, whereas bonds, shipping, CLOs and crude oil absorb the spread shocks. Moreover, we evaluate the hedging ability of CLOs within a portfolio of inflation hedges by estimating hedge ratios and optimal weights by utilizing conditional variance estimations (DCC). Our results indicate that CLOs possess impeccable hedging ability, as the short position in their volatility provides high hedging effectiveness for all investors holding long-positions in the volatility of the remaining assets. Our analysis highlights the importance of CLOs and their relevance to portfolio diversification.